Pengaruh Promosi Jabatan dan Punishment terhadap Disiplin Kerja Karyawan PT Fajar Indah Anindya Medan - Wie Shi Sudjud (Pusat Riset dan Inovasi Nasional, 2021)
This research was conducted at PT Fajar Indah Anindya Medan. The level of work discipline that can be seen from the delay and absence of employees. Job promotion systems that are still based on seniority are not based on work performance and employee discipline. Punishment that has not been resolute to employees. The population and sample in this study were 42 employees. The sampling technique used is saturated samples Data collection techniques are pembainigain kueisoner, interviews and documentation studies. Data analysis uses validity and reliability test, classic assumption test, multiple linear regression analysis, determinant coefficient and hypothesis testing.Conclusions in the study that simultaneous job promotion and punishment affect the work discipline of employees of PT Fajar Indah Anindya Medan. Partially, job promotion influences the work discipline of PT Fajar Indah Anindya Medan employees. Partially punishment affects the work discipline of PT Fajar Indah Anindya Medan employees. The magnitude of the determination coefficient that the adjusted R Square value is 0.502 means that promotion and punishment can explain employee discipline at 50.2% and the remaining 49.8% (100-50.2) influenced by other variables outside of this study such as: compensation, leadership and supervision of work and so on